Necesidad de reformar la ley de gestión ambiental con la finalidad de crear unidades de gestión ambiental de forma obligatoria en todas las instituciones públicas respecto al artículo 13 - Peña Jaramillo, Francisco Javier (2016)
The deterioration of the environment is a cause of degradation of human well-being in the world; in underdeveloped countries, as in the case of Ecuador, environmental degradation is linked to poverty as a cause and effect; This phenomenon has been noted in almost all the multilateral and national meetings who have treated the subject, in addition to being easy to empirical verification. To control environmental deterioration and its sequel on society, the Ecuador has incorporated the environmental principles of the modern world in the Constitution of the Republic and has created laws and institutions for environmental management; These authorize, delegate and oblige certain institutions such as the Ministry of the environment, as the principal, who is in charge of exercising environmental control functions Hence, the Constitution provides in its article 15 that: "the State will promote, in the public and private sectors, the use of environmentally clean technologies and non-polluting alternative energies and low impact. Energy sovereignty will not be achieved at the expense of food sovereignty, or affect the right to water. Prohibits development, production, possession, marketing, import, transport, storage and use of weapons nuclear, biological and chemical contaminants organic persistent highly toxic, internationally banned, agro-chemicals and technologies and experimental harmful biological agents and genetically modified organisms that are harmful to human health or ecosystems or threaten food sovereignty, as well as the introduction of nuclear waste and toxic waste to the country 6 The Ecuadorian Municipalities are required by the environmental management Act, through legal provisions, to establish units specializing in environmental management within their public institutions. While in the law on environmental management, in its art. 13 determines that "provincial councils and municipalities, will give a sectional environmental policies subject to the political Constitution of the Republic and the present law. They shall comply with national regulations on the heritage of protected natural Areas to determine the land use and consult the representatives of indigenous peoples, Afro-Ecuadorians and local populations to the delimitation, handling and management of conservation areas and ecological reserve. The structuring of specialized units not has been realized in the small municipalities of the country, i.e. in the cantons with less than 100,000 inhabitants; in other cases, these units are in the process of structuring or have only been partially established or are dysfunctional; in the private sector there is no exception of cobbling together studies of environmental management professionals, which in some cases are not studied nor experts in the branch. So the field of environmental management, it becomes a source of jurisdictional conflicts within a complex institutional landscape by imprecision, vagueness or dismantling of the laws. This is why the need to propose a thesis research to propose an urgent reform to the environmental management Act, in terms of establishing mandatory creation of permanent environmental management units in all public institutions related to the conservation and utilization of natural resources.